2012
DOI: 10.1369/0022155412443542
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sigma1 Receptor and Its Positive Associations With Pathologic TNM Classification in Esophageal Squamous Cell Carcinoma

Abstract: SummarySigma1 receptor (sigma1R), a significant protein, has been found to be frequently upregulated in human tumor cells and tissues. It has been demonstrated that sigma1R is involved in proliferation and adhesion of cancer cells. However, the significance of sigma1R expression in esophageal squamous cell carcinoma (ESCC) remains unclear. In this article, by a series of methods, the authors examined the expression of sigma1R protein in ESCC cell lines and tissues. Flow cytometry indicated intense staining of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…A novel finding in the present study was that σ1R was expressed at low levels in HCC, and that there was a statistically significant difference between its expression levels in benign hepatic tissue and HCC (P<0.01). The decreased expression of σ1R in HCC was an interesting phenomenon, which was inconsistent with former studies in other tumor types (16,18,25). We considered that this contradiction may indicate a different molecular biological function in HCC compared with other tumor types.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…A novel finding in the present study was that σ1R was expressed at low levels in HCC, and that there was a statistically significant difference between its expression levels in benign hepatic tissue and HCC (P<0.01). The decreased expression of σ1R in HCC was an interesting phenomenon, which was inconsistent with former studies in other tumor types (16,18,25). We considered that this contradiction may indicate a different molecular biological function in HCC compared with other tumor types.…”
Section: Discussioncontrasting
confidence: 65%
“…Additionally, the upregulation of σ1R was reported to correlate with the biological behavior of tumors, such as proliferation, adhesion and cell death (14,16). Our previous study showed that σ1R was overexpressed in human esophageal squamous cell carcinoma and that the overexpression of σ1R was significantly associated with the pathological TNM classification and lymph node metastasis (18). However, the expression of σ1R and its biological relevance in HCC have not yet been identified.…”
Section: Introductionmentioning
confidence: 98%
“…Immunohistochemistry was performed using 2-step protocol according to the manufacturer’s instructions (PV-9000 Polymer Detection System, ZSGB-BIO, Beijing, China) as described previously [ 15 ]. Rabbit polyclonal antibodies against p53, NY-ESO-1, MMP-7, Hsp70, PRDX6, and Bmi-1 (all 1:200; Immunosoft, Zhoushan, China) were incubated overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…TMA construction has been described in our previous studies [37-40]. Two tissue cores of 1.8 mm in diameter were taken from the donor blocks and transferred to the recipient paraffin block at defined array positions.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was carried out by a two-step protocol (PV-9000 Polymer Detection System, ZSGB-BIO, Beijing, China) as previously described [40]. …”
Section: Methodsmentioning
confidence: 99%